Instrumen Pengukuran Kinerja Inovasi Perusahaan Kontraktor di Indonesia - Julison, Bernathius (MEDIA KOMUNIKASI TEKNIK SIPIL, 2014)
Within the framework of the company's innovation theory, the purpose of this research is to develop an instrument to measure the performance of innovation activities of construction companies in Indonesia. The performance of innovation activities of construction companies is measured based on its innovation index and its sustainable competitive advantage index, and stratified by qualification of construction companies (small, medium, and large). The company's innovation index is calculated based on the analysis of inputs, processes, outputs, outcomes and impact of the innovation. Company's sustainable competitive advantage index is calculated based on (1) the company's ability to maintain and improve its competitive advantage indicators in the last five years, and (2) the degree of scarcity, imitate difficulty, and replaced difficulty or unreplaceability of the output of innovation activities. Indicator of a company's competitive advantage that calculated in this study is the profitability, productivity and market share of the company